1999
DOI: 10.1002/(sici)1097-0142(19990301)85:5<1166::aid-cncr22>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Hodgkin disease

Abstract: BACKGROUND Hodgkin disease rarely presents as an osseous lesion, and the majority of patients are found at staging to have concurrent disease in lymph nodes. Many cases of osseous Hodgkin disease have been misdiagnosed on initial biopsy. METHODS All cases of Hodgkin disease diagnosed by open bone biopsy at the Mayo Clinic were identified. These included patients with primary osseous tumors, those presenting with multiple sites of involvement (with osseous lesions), and those with recurrence in bone. Recut sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 32 publications
0
64
0
6
Order By: Relevance
“…We also found that, as in adults, 2,3,18 BM involvement did not significantly affect the relapse-free survival or overall survival of patients with stage IV HL, nor did it carry any prognostic disadvantage in stage IV HL. 25,26 This finding is extremely important because in some low-income countries, patients with BM involvement at diagnosis may be incorrectly deemed incurable, and curative frontline therapy or radiotherapy may be withheld. Furthermore, neither the site of extranodal disease (bone, lung, or liver) nor the number of extranodal sites (1, 2, 3, or 4) significantly affected the relapse-free or overall survival of patients with stage IV HL.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, as in adults, 2,3,18 BM involvement did not significantly affect the relapse-free survival or overall survival of patients with stage IV HL, nor did it carry any prognostic disadvantage in stage IV HL. 25,26 This finding is extremely important because in some low-income countries, patients with BM involvement at diagnosis may be incorrectly deemed incurable, and curative frontline therapy or radiotherapy may be withheld. Furthermore, neither the site of extranodal disease (bone, lung, or liver) nor the number of extranodal sites (1, 2, 3, or 4) significantly affected the relapse-free or overall survival of patients with stage IV HL.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma and Ewing sarcoma are most often involved, but the dierential diagnosis also includes non-Hodgkin lymphomas, leukemia, metastatic lesions, Langerhans cell histiocytosis, and a variety of benign tumors [4,5].…”
Section: Discussionmentioning
confidence: 59%
“…Histologic diagnosis of osseous HL can also be very problematic, undoubtedly because of the rarity of HL in the bones. Immunohistochemical stains are very helpful in diagnosing this tumor [5].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases have been associated with synchronous lymph node involvement. Since 1927, only seven patients with primary solitary osseous HD [6,19,26,31,32,33] and five patients with primary multifocal osseous Hodgkin disease have been reported without lymphatic manifestations [13,16,29,31]. Two of these cases, which have been reported before 1944, presented limited clinical and radiographic evalu- ations.…”
Section: Discussionmentioning
confidence: 99%
“…In late stage HD, osseous localizations have been described in 10-20% of cases [3,10,17,20,24,30], with less then 2% of cases showing skeletal lesions at the time of initial presentation. To our knowledge multifocal primary osseous HD without lymphatic manifestations has been reported only in five cases [13,16,29,31]. This article describes one further case and reviews the literature with special emphasis on treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%